2003
DOI: 10.5367/000000003101294244
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Yam Domestication and Farmers' Practices in Benin and Nigeria

Abstract: This paper combines the results of surveys carried out between 1995 and 2001 in Benin and Nigeria on farmers' practices in connection with the domestication of yams (Dioscorea rotundata), which is still an active process in West Africa. In Benin more than 500 yam producers belonging to four major yamproducing ethnic groups (Bariba, Mahi-Fon, Nago and Yom) and nearly 300 farmers in six different states of Nigeria were interviewed. The knowledge of wild yams is still alive even among farmers who have never domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 4 publications
1
18
1
3
Order By: Relevance
“…This result was in accordance with those reported by Vernier et al (2003) but contrary to those reported by Baco who previously identified three morphotypes (Baco, 2000) in the same cultural area. This variation in the number of domesticable morphotypes reflects the lack of control of the phenomenon of the domestication by a large number of farmers (Baco, 2000;Vernier et al, 2003). Likewise, the domestication could be considered as a subjective phenomenon because what is domesticable for some farmers is not always for others.…”
Section: Sampling and Morphological Variabilitycontrasting
confidence: 56%
See 1 more Smart Citation
“…This result was in accordance with those reported by Vernier et al (2003) but contrary to those reported by Baco who previously identified three morphotypes (Baco, 2000) in the same cultural area. This variation in the number of domesticable morphotypes reflects the lack of control of the phenomenon of the domestication by a large number of farmers (Baco, 2000;Vernier et al, 2003). Likewise, the domestication could be considered as a subjective phenomenon because what is domesticable for some farmers is not always for others.…”
Section: Sampling and Morphological Variabilitycontrasting
confidence: 56%
“…Likewise, the domestication could be considered as a subjective phenomenon because what is domesticable for some farmers is not always for others. (Vernier et al 2003), they were genetically closer to the latter species whose control used is in this study clustered in the same group. Thus, the real genetic nature of non domesticable D. abyssinica deserves to be studied more thoroughly.…”
Section: Sampling and Morphological Variabilitymentioning
confidence: 81%
“…Indeed, conjointly with the exchange of cultivars, farmers always use the domestication of wild yams to mitigate genetic erosion due to the vegetal multiplication of the cultivated yams (Trèche 1996;Dumont and Vernier 2000;Vernier et al 2003;Mignouna and Dansi 2003). Thus, there exists a co-evolution between wild (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was not clear until recently when numerous studies using powerful tools (such as enzymatic and molecular markers; flow cytometry) were carried out to understand the relationship between D. rotundata and wild yams. In addition, social surveys carried out in Benin (Dumont and Vernier 1997) and Nigeria (Vernier et al 2003) showed similar practices of domestication by farmers in these regions. Hildebrand (2003) also reported a similar kind of domestication process in southwestern Ethiopia where several wild yams have been brought under cultivation.…”
Section: Domestication Of Yams In West Africamentioning
confidence: 99%